Transforming Proofreading into Profits: Entrepreneurship Opportunities in English Education - Waluyo, Gatot Hadi; Adawiyah, Dita; Muazza, Muazza (PPSDP International Journal of Education, 2024)
This study looks at how the increasing use of English worldwide affects the proofreading industry, which is expected to grow to a $72.1 billion market by 2023. It examines the strategies used by business owners to start and grow their proofreading businesses, especially as the demand for flawless proofreading services increases. These services are crucial for making texts clear, well-organized, and accurate. Facing issues like too many businesses entering the market and rapid technological changes, this research aims to identify successful ways for businesses to stand out and adapt. The study uses detailed research methods, such as in-depth reviews of theories on starting a business, market trends, competition, and technology. It suggests that proofreading businesses should focus on specific areas, use technology to work more efficiently and accurately, and make sure they deliver quality work quickly. The research highlights the importance of always learning, keeping up with new technology, and listening to what customers have to say as key ways to stay competitive in a changing market. These suggestions provide a guide for beginners in the proofreading industry on how to be successful and maintain their business over time. By following these guides, new businesses can handle the challenges of the market and position themselves well among competitors.